Non-Linear Finite Element Analysis of Flexural Reinforced Concrete Beam using Embedded Reinforcement Modeling - Mahmud Kori Effendi (Journal of the Civil Engineering Forum, 2020)
Reinforced concrete is one of the most widely used building materials in Indonesia due to its workability, easiness, and reasonable price. Meanwhile, it is very important to understand the response of these elements during the loading process to ensure the development of an effective structure and one of the most effective numerical methods for reinforced concrete elements is the Finite Element Analysis (FEA). This study was, therefore, conducted to investigate the flexural behavior of reinforced concrete beam using a nonlinear finite element analysis through the application of the MSC MARC/MENTAT software program. This involved the use of a solid element to represent concrete while the truss bar was applied for reinforcing steel after which multi-linear and bilinear models were considered for the two elements respectively while embedded reinforcement model was applied to model the rebar. Moreover, the beam model was also studied and compared with experimental data from previous literature. The result showed the load-deflection to have significantly increased due to an increment in the steel reinforcement yield strength. The same was also observed for the concrete compressive strength while a decrease was recorded in deflection due to the reduction in the compressive strength because the strain was reaching the crushing value. Furthermore, the concrete tension model was found to be the same with the experimental results with the tensile strength observed to have lost its strength after reaching the tensile stress while the contact behavior of the modeled reinforced concrete beam showed the existence of a slip at the support and loading points.